2012
DOI: 10.1039/c2cp40821j
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of a variety of organic photovoltaic devices by IPCE and in situ IPCE analyses – the ISOS-3 inter-laboratory collaboration

Abstract: This work is part of the inter-laboratory collaboration to study the stability of seven distinct sets of state-of-the-art organic photovoltaic (OPV) devices prepared by leading research laboratories. All devices have been shipped to and degraded at RISØ-DTU up to 1830 hours in accordance with established ISOS-3 protocols under defined illumination conditions. In this work, we apply the Incident Photon-to-Electron Conversion Efficiency (IPCE) and the in situ IPCE techniques to determine the relation between sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 61 publications
2
44
0
Order By: Relevance
“…Water release from PEDOT:PSS was suggested in the previous ISOS-3 reports. 16,17 The relative performance over time suggests significantly different degradation behaviour for the two devices, which is further supported by significantly different lifetimes. Photo-oxidation was most likely not an important factor for the overall device degradation, so other factors must have been in play for the ISE and Holst devices such as for example the degradation mechanisms proposed in the second and third ISOS-3 reports.…”
Section: Glass/metal Encapsulation -Ise and Holst Devicesmentioning
confidence: 88%
See 3 more Smart Citations
“…Water release from PEDOT:PSS was suggested in the previous ISOS-3 reports. 16,17 The relative performance over time suggests significantly different degradation behaviour for the two devices, which is further supported by significantly different lifetimes. Photo-oxidation was most likely not an important factor for the overall device degradation, so other factors must have been in play for the ISE and Holst devices such as for example the degradation mechanisms proposed in the second and third ISOS-3 reports.…”
Section: Glass/metal Encapsulation -Ise and Holst Devicesmentioning
confidence: 88%
“…If photo-oxidation was not an important factor for the overall degradation, then other factors must have been in play for the ISE and Holst devices such as those suggested in the second and third ISOS-3 reports. 16,17 In the second ISOS-3 report it was suggested that for the Holst device elevated temperatures (85 AE 5 1C) caused by the sun simulator and additional heating of the cell due to current collection within the PEDOT:PSS could result in water being released from the highly conductive PEDOT:PSS, which consequently would react with the Al electrode, forming aluminium oxide. 16 Furthermore, in the third ISOS-3 report an additional degradation mechanism was proposed for the Holst device.…”
Section: Glass/metal Encapsulation -Ise and Holst Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The demonstration of power conversion efficiencies (PCEs) over 10% and continuously improving in research cells from a variety of materials systems is a major achievement [4]. The issue of cell lifetime and an understanding of cell degradation have also been addressed in some laboratory studies [5][6][7][8][9][10][11][12], and a few outdoor tests [13][14][15]. Of the three major attributes needed, lifetime in realistic outdoor settings is probably the most significant challenge left to address.…”
Section: Introductionmentioning
confidence: 99%